Beiträge zur Klimakunde von Hochasien - Flohn, Hermann (ERDKUNDE, 1958)
On the basis of all available data (including expedition observations at various places) climatological averages were derived for Tibet and adjacent parts of the Central Asiatic Highlands. Owing to the elevated insolation surface, the temperatures of the high plateau are about 4-9°C higher during the warm season than the latitudinal average of the free atmosphere, while the humid valleys and slopes of the Himalayas remain remarkably cool, despite their lower elevation. The daily periodicity of the winds and the frequency of gales can be explained by vertical momentum exchange and the fact that the highlands reach into the sub-tropical jet streams. The complicated precipitation mechanism consists of specific weather situations, dynamic effects and local diurnal winds. Within the general atmospheric circulation, the block of High Asia acts as a mechanical obstacle and also during the warm season as a source of heat; its hypothetical effect as a source of cold air during the winter is however doubtful. The different climatic types were classified according to Köppen’s system.